1998
DOI: 10.3168/jds.s0022-0302(98)75890-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Conjugated cis-9, trans-11-Octadecadienoic Acid in Bovine Milk Because of Dietary Supplementation

Abstract: Cows on pasture were fed full fat soybeans (toasted, flaked, and pelleted) or ground full fat rapeseeds to investigate effects on cis-9, trans-11-octadecadienoic acid in milk. Three herds of 16 cows each that were on pasture were fed 3.1 kg/d of unmolassed beet pulp (control), 3.0 kg/d of rapeseed concentrate, or 3.1 kg/d of a soybean supplement. The concentration of cis-9, trans-11-octadecadienoic acid in the milk of cows fed the rapeseed and soybean supplements was significantly higher than in the milk of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
3
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 16 publications
10
72
3
7
Order By: Relevance
“…Unlike what happens with diets composed of conserved forage and variable proportions of concentrates, there is less information in the literature concerning the effect of oils or vegetable seed supplementation of diets on the concentrations of CLA and TVA in the milk fat of grazing dairy cows. Stanton et al [18] and Lawless et al [9] reported significant increases in the concentrations of CLA and TVA in the milk fat of grazing cows directly related to the amount of FFS and FFR supplemented, which were supported by the results of the present study. Partially replacing maize grain by CaFA in the concentrate supplemented to grazing dairy cows, increased the CLA content in milk fat by 58% [20] and by 173% [16].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Unlike what happens with diets composed of conserved forage and variable proportions of concentrates, there is less information in the literature concerning the effect of oils or vegetable seed supplementation of diets on the concentrations of CLA and TVA in the milk fat of grazing dairy cows. Stanton et al [18] and Lawless et al [9] reported significant increases in the concentrations of CLA and TVA in the milk fat of grazing cows directly related to the amount of FFS and FFR supplemented, which were supported by the results of the present study. Partially replacing maize grain by CaFA in the concentrate supplemented to grazing dairy cows, increased the CLA content in milk fat by 58% [20] and by 173% [16].…”
Section: Resultssupporting
confidence: 81%
“…The concentration of oleic acid and its different cis/trans isomers (including trans-10 C 18:1 ) significantly (P < 0.05) increased in the milk fat of cows supplemented with VO as a likely consequence of the rumen biohydrogenation process of linoleic and linolenic FA present in the diet and due to the desaturation of stearic acid in the mammary gland [4]. These results are globally supported by data reviewed by Schroeder et al [17] and by the works of Murphy et al [11], Lawless et al [9], Vidaurreta et al [20] and Schroeder et al [16], leaving cows feeding on pasture. All these authors used oleaginous seeds treated or not, or calcium salts of fatty acids (CaFA), which provide a reduced degree of protection of long chain unsaturated fatty acids to the biohydrogenation in the rumen.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Milk yield and milk fat content tended to increase when oilseeds rather than vegetable oils were fed to not grazing dairy cows [26] but such positive effects were not detected when lipid treatments were compared to control rations without oils seeds [25] [26] [27]. In our experiment, milk yield tended to be higher (13%) in sunflower oil treatments ( Table 7) a result that differed from [26].…”
Section: Milk Production and Compositioncontrasting
confidence: 51%